2021
DOI: 10.1038/s42003-021-02039-8
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of ABCG5/G8 in complex with modulating antibodies

Abstract: The heterodimer of ATP-binding cassette transporter ABCG5 and ABCG8 mediates the excretion of sterols from liver and intestine, playing a critical role in cholesterol homeostasis. Here, we present the cryo-EM structure of ABCG5/G8 in complex with the Fab fragments from two monoclonal antibodies at 3.3Å resolution. The high-resolution structure reveals a unique dimer interface between the nucleotide-binding domains (NBD) of opposing transporters, consisting of an ordered network of salt bridges between the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…5 a). An ABCG5/ABCG8 structure with a correct registry was also released on 2021-04-07 (PDBID: 7jr7 [ 32 ]), but AF2 template search for building models deposited at EBI used pdb70 downloaded on 2021-02-10 [ 5 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…5 a). An ABCG5/ABCG8 structure with a correct registry was also released on 2021-04-07 (PDBID: 7jr7 [ 32 ]), but AF2 template search for building models deposited at EBI used pdb70 downloaded on 2021-02-10 [ 5 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This was demonstrated for other ABC transporters as well, e.g. , ABCB1 [102] , ABCB2 [103] , ABCB6 [122] , ABCB11 [123] , ABCC7 [124] , ABCC8 [105] , ABCG2 [106] , and ABCG5/G8 [125] , forming either an inward-facing [105] , [106] , [122] , [123] , [124] , [125] or (drug-induced) occluded [102] , [103] conformation. In contrast, most ABC transporters in the ATP-bound state are not able to recognize substrates, as shown for ABCB4 [104] , as these form an outward-facing conformation.…”
Section: Resultsmentioning
confidence: 79%
“…4A/B ). As current apo or ATP-bound structures of ABCG sterol transporters are rather limited to early and end states of catalysis (Lee et al, 2016; Skarda et al, 2021; Sun et al, 2021; Zhang et al, 2021), the sterol poses as observed here may represent the post-efflux conformations as the hydrophobic valve has already been resealed in these ATP-bound structures. For this reason, binding sites within the protein were unable to be detected and subsequently docked.…”
Section: Resultsmentioning
confidence: 83%
“…Three X-ray diffraction datasets were integrated and scaled with acceptable statistics. The initial model was obtained by molecular replacement using a previously resolved cryo-EM structure (PDB ID: 7JR7) (Zhang et al, 2021), and the motifs involved in ATP binding were adjusted based on the previous crystal structure (PDB ID: 5DO7) (Lee et al, 2016). Two ABCG5/G8 heterodimers are observed in the asymmetric unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation